A Single‐Molecule and Logic Gate via Optical and Acid–Base Control. Issue 10 (7th September 2020) - Zhao, Wenkai; Zou, Dongqing; Sun, Zhaopeng; Xu, Yuqing; Ji, Guomin; Li, Xiaoteng; Yang, Chuanlu
Abstract: Single‐molecule electronics is a promising solution for electronic device miniaturization. While controllable molecular logic gates are particularly attractive because they are the primary element and can accomplish logical operation reliable and repeatedly for practical application. Here, a brand‐new molecule, which is constructed from a light‐switchable azobenzene unit and proton‐switchable pyrimidine unit, is reported. The electronic transport properties of the molecule are theoretically investigated by density functional theory (DFT) combined with non‐equilibrium Green's function method (NEGF). The calculated current–voltage curves show that the molecule system produces a low resistance only when the ultraviolet (UV) light and acid solution are applied, otherwise, a high resistance will be obtained. Therefore, the molecule system can behave as a single‐molecule AND logic gate which can be controlled by two orthogonal inputs: protonation and light. This work demonstrates a feasible perspective for creating single‐molecule logic gate device. Abstract : Using density functional theory combined with non‐equilibrium Green's function method, the molecule (E)‐5‐(3‐(phenyldiazenyl)‐[1, 1′‐biphenyl]‐4‐yl) pyrimidine (PDBP), which mainly contains two moieties: azobenzene unit and pyrimidine unit, can behave as a single‐molecule AND logic gate, which can be controlled by two orthogonal inputs: protonation and light. This work demonstrates a feasible perspective for creating single‐molecule logic gate device.